Information and Communication Technology Proceedings of ICICT 2016 - Mishra, Durgesh Kumar; Azar, Ahmad Taher; Joshi, Amit.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book volume contains 31 papers presented at ICICT 2016: Second International Congress on Information and Communication Technology. The conference was held during 12-13 December 2016, Bangkok, Thailand and organized communally by G R Foundation, and Computer Society of India Division IV - Communication and Division V - Education and Research. This volume contains papers mainly focused on ICT for computation, algorithms and data analytics, and IT security.
Preface -- About the editors -- Table of Contents -- 32 Chapters -- Author index.
Keywords: Telecommunication; Data mining; Data protection; Communications Engineering, Networks; Data Mining and Knowledge Discovery; Data and Information Security